Comparative Study between RIPASA Scoring System and ALVARADO Scoring System in Diagnosing Acute Appendicitis in Adults - Aous Hameed; Hameed Hussein Alaraji (مجله كليه طب الكندي, 2023)
Background: Acute appendicitis is regarded as one of the most common inflammation that needs surgical intervention. Different scoring systems have been used for diagnosing of acute appendicitis. ALVARADO score is one of the most widely used score in diagnosing of acute appendicitis, but the accuracy of the latter is insufficiently low in Middle-East patients. Thus a new scoring system called RIPASA score has been designed for diagnosing of acute appendicitis in those patients. The aim of this study is to use RIPASA score and compare its result with ALVARADO score in diagnosing of acute appendicitis.